Active video games in fully immersive virtual reality elicit moderate-to-vigorous physical activity and improve cognitive performance in sedentary college students - Caio Victor Sousa; Jungyun Hwang; Romina Cabrera-Perez; Austin Fernandez; Aika Misawa; Kelsey Newhook; Amy Shirong Lu (Elsevier, 2022)
Background: Active video games are a new method for increasing physical activity (PA). Fully immersive virtual reality (VR) is a hardware device on which an active video game can run. Active (video games in) VR (AVR), might increase immersion, game engagement, and moderate-to-vigorous PA (MVPA), thereby yielding greater exercise-related benefits, e.g., cognitive performance. Methods: We examined the induction of MVPA via an AVR and a sedentary VR (SVR) as well as the effects of VR play on cognitive performance, which was monitored using 2 different methods. Each of 29 sedentary college students attended three 20-min laboratory sessions (AVR, SVR, or control) in a randomized order; during the control session, they sat quietly doing nothing. A fully immersive headset was used for the 2 video game sessions. We monitored and computed participants' PA using hip-worn accelerometers (wGT3x-bt; ActiGraph, Pensacola, FL, USA) and a heart rate band (Polar H7; Polar, Kempele, Finland). After each session, the participants completed a mnemonic similarity test (MST) to measure recognition memory. They also filled out a motion sickness questionnaire and an abbreviated game experience questionnaire. Results: The AVR session induced a significantly greater heart rate and more time spent in MVPA than did either of the other 2 sessions regardless of the PA monitoring method. AVR elicited greater game experience questionnaire-assessed sensory and imaginative immersion, challenge, and positive affect than did SVR. The mnemonic similarity test recognition score was marginally higher post-AVR session than it was post-SVR session. Conclusion: AVR elicited MVPA without a significant increase in motion sickness and induced a better game experience and better borderline cognitive performance than did SVR.